2015
DOI: 10.1103/physrevd.92.115018
|View full text |Cite
|
Sign up to set email alerts
|

Vectorlike leptons at the Large Hadron Collider

Abstract: We study the prospects for excluding or discovering vectorlike leptons using multilepton events at the LHC. We consider models in which the vectorlike leptons decay to tau leptons. If the vectorlike leptons are weak isosinglets, then discovery in multilepton states is found to be extremely challenging. For the case that the vectorlike leptons are weak isodoublet, we argue that there may be an opportunity for exclusion for masses up to about 275 GeV by direct searches with existing LHC data at sqrt{s}=8 TeV. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
122
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(128 citation statements)
references
References 69 publications
(55 reference statements)
6
122
0
Order By: Relevance
“…For small values of | sin θ|, radiative corrections to λ 111 dominate the corrections to the SM h 1 h 1 production cross-section, as opposed to the leading order mixing angle effects reflected in figures 6-7 (which are important for larger | sin θ|). 7 There are more sophisticated methods to calculate exclusion and discovery in the presence of systematic uncertainties [96][97][98]. However, for for simplicity we adopt the prescription that the systematic uncertainties are subdominant for S/B 0.1. .…”
Section: Additional Probesmentioning
confidence: 99%
“…For small values of | sin θ|, radiative corrections to λ 111 dominate the corrections to the SM h 1 h 1 production cross-section, as opposed to the leading order mixing angle effects reflected in figures 6-7 (which are important for larger | sin θ|). 7 There are more sophisticated methods to calculate exclusion and discovery in the presence of systematic uncertainties [96][97][98]. However, for for simplicity we adopt the prescription that the systematic uncertainties are subdominant for S/B 0.1. .…”
Section: Additional Probesmentioning
confidence: 99%
“…al. showed that if the VL lepton decays only to τ , then the bound may only be M e4 275 GeV [15]. Due to the sampling method that we explain below, VL leptons in this model can either be predominantly E L,R or L L,R , depending on model parameters.…”
Section: Methodsmentioning
confidence: 99%
“…There are more recent bounds on the mass of VL leptons obtained from reinterpreting ATLAS and CMS experiments [12][13][14][15]. If the lightest VL lepton is predominantly E L,R , then the bound is similar to the LEP bound.…”
Section: Methodsmentioning
confidence: 99%
“…These were studied in a phenomenological context in [53]. However the two benchmarks models considered in their study correspond roughly to the SUð2Þ L singlet (and doublet models) of Eq.…”
Section: Simplified Fermionic Modelsmentioning
confidence: 99%